MP06: Impact of anticoagulation on mortality and resource utilization among critically ill patients with major bleeding in the emergency department. (May 2019) - Mok, G.; Fernando, S.; Castellucci, L.; Dowlatshahi, D.; Rochwerg, B.; McIsaac, D.; Carrier, M.; Wells, P.; Bagshaw, S.; Tanuseputro, P.; Kyeremanteng, K.
Abstract : Introduction : Patients with major bleeding (e.g. gastrointestinal bleeding, and intracranial hemorrhage [ICH]) are commonly encountered in the Emergency Department (ED). A growing number of patients are on either oral or parenteral anticoagulation (AC), but the impact of AC on outcomes of patients with major bleeding is unknown. With regards to oral anticoagulation (OAC), we particularly sought to analyze differences between patients on Warfarin or Direct Oral Anticoagulants (DOACs).Methods : We analyzed a prospectively collected registry (2011-2016) of patients who presented to the ED with major bleeding at two academic hospitals. "Major bleeding" was defined by the International Society on Thrombosis and Haemostasis criteria. The primary outcome, in-hospital mortality, was analyzed using a multivariable logistic regression model. Secondary outcomes included discharge to long-term care among survivors, total hospital length of stay (LOS) among survivors, and total hospital costs.Results : 1, 477 patients with major bleeding were included. AC use was found among 215 total patients (14.6%). Among OAC patients (n = 181), 141 (77.9%) had used Warfarin, and 40 (22.1%) had used a DOAC. 484 patients (32.8%) died in-hospital. AC use was associated with higher in-hospital mortality (adjusted odds ratio [OR]: 1.50 [1.17-1.93]). Among survivors to discharge, AC use was associated with higher discharge to long-term care (adjusted OR: 1.73 [1.18-2.57]), prolonged median LOS (19 days vs. 16 days, P = 0.03), and higher mean costs (69, 273 vs. 58, 156, P = 0.02). With regards to OAC, a higher proportion of ICH was seen among patients on Warfarin (39.0% vs. 32.5%), as compared to DOACs. No difference in mortality was seen between DOACs and Warfarin (adjusted OR: 0.84 [0.40-1.72]). Patients with major bleeding on Warfarin had longer median LOS (11 days vs. 6 days, P = 0.03) and higher total costs (51, 524 vs. 35, 176, P < 0.01) than patients on DOACs.Conclusion : AC use was associated with higher mortality among ED patients with major bleeding. Among survivors, AC use was associated with increased LOS, costs, and discharge to long-term care. Among OAC patients, no difference in mortality was found. Warfarin was associated with prolonged LOS and costs, likely secondary to higher incidence of ICH, as compared to DOACs.